P8. Information flow between hippocampus and sensory cortex reverses during working memory maintenance. Issue 8 (August 2021) - Dimakopoulos, V.; Boran, E.; Hilfiker, P.; Stieglitz, L.; Grunwald, T.; Megevand, P.; Sarnthein, J.
Abstract : Background. The maintenance of items in working memory (WM) relies on a widespread network of brain areas where the mode of functional coupling is debated. Methods. N = 4 epilepsy patients read and heard a string of letters and then maintained it in WM while we recorded sEEG from the hippocampus, temporo-parietal ECoG from grid electrodes, and scalp EEG. Results. We evaluated the local cognitive processing with power spectral density (PSD). The PSD in the posterior parietal lobe (∼20 Hz alpha band) and in the hippocampus peaked towards the end of the maintenance period in expectance of the probe. Inter-area oscillatory coupling (PLV) in the theta/alpha range increased from hippocampal sEEG to ECoG and scalp EEG. The information flow (Granger causality) was from auditory cortex to hippocampus in the 8-18 Hz range while letters were presented, and this flow was subsequently reversed during maintenance, while letters were maintained in WM. Conclusions. The functional interaction between hippocampus and cortex through synchronized oscillatory activity increased specifically during maintenance. The directed information flow provides a physiological basis for the reverberation of memory items during maintenance.